2001
DOI: 10.1093/ajcn/73.5.900
|View full text |Cite
|
Sign up to set email alerts
|

Lysine requirements of healthy adult Indian subjects, measured by an indicator amino acid balance technique

Abstract: We propose a mean lysine requirement of 30 mg x kg(-1) x d(-1) for healthy Indian adults, which is the same amount we proposed previously for Western populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 34 publications
3
37
0
Order By: Relevance
“…In this study, the inflection point of the decreasing speed of force-time curve was calculated statistically to distinguish between a marked decreasing phase and an almost steady state phase. Many researchers (Kurpad et al, 2001;Lee et al, 1990;Soler et al, 1989) have proposed a method to examine the inflection point (break point) statistically by applying a two-phase regression model to time series data that can assume two phases. The inflection point was the time at which the decreasing speed of force exertion remarkably changed, and it was calculated statistically from two regression lines fitted to each decreasing phase by applying this model.…”
Section: Force-time Parametersmentioning
confidence: 99%
“…In this study, the inflection point of the decreasing speed of force-time curve was calculated statistically to distinguish between a marked decreasing phase and an almost steady state phase. Many researchers (Kurpad et al, 2001;Lee et al, 1990;Soler et al, 1989) have proposed a method to examine the inflection point (break point) statistically by applying a two-phase regression model to time series data that can assume two phases. The inflection point was the time at which the decreasing speed of force exertion remarkably changed, and it was calculated statistically from two regression lines fitted to each decreasing phase by applying this model.…”
Section: Force-time Parametersmentioning
confidence: 99%
“…The risk of lysine inadequacy is high where low socioeconomic groups depend on wheat for their protein supply (1), but experimental evidence of the nutritional benefits of increasing the lysine content of wheat flour is limited (2)(3)(4)(5)(6)(7)(8). This study, which was a part of a larger wheat fortification trial, was based on a hypothesis that fortification of a lysine inadequate diet in poor communities may reduce anxiety and improve stress response, thereby potentially improving the quality of life.…”
mentioning
confidence: 99%
“…In infancy, inadequate protein (based on animal studies) would be expected to affect growth of lean mass and length/ height, and in adults, functional studies such as those measuring glutathione homeostasis are relevant (Jackson et al, 2004). We have shown that muscle strength declines with low levels of lysine intake, and is improved when generous intakes of lysine are eaten over a longer period (3 weeks and 8 weeks, Kurpad et al, 2002;Unni et al, 2012). In addition, recent evidence on lower plasma amino acid levels in undernourished children is also indicative of the role amino acids may play in growth (Semba et al, 2016).…”
Section: Amino Acid Requirementmentioning
confidence: 87%